1995
DOI: 10.2307/3587625
|View full text |Cite
|
Sign up to set email alerts
|

A Closer Look at Learning Strategies, L2 Proficiency, and Gender

Abstract: This study builds on previous research using the Strategy Inventory for Language Learning (SILL). Most previous SILL research has made comparisons across the entire survey or in terms of strategy categories and has stressed proficiency level at the expense of other variables. The present largescale (N = 374) study of language learning strategy use by students at three different course levels at the University of Puerto Rico relates strategy use to gender as well as to L2 proficiency level and includes analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

80
600
14
37

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 701 publications
(731 citation statements)
references
References 32 publications
(30 reference statements)
80
600
14
37
Order By: Relevance
“…Oxford (2003) reports on multiple studies that have used her Strategy Inventory for Language Learning (SILL) to measure the relationship between strategy use and proficiency. Most have found the relationship to be of either a linear (e.g., Green & Oxford, 1995;Oxford & Ehrman, 1995) or curvilinear nature (e.g., Phillips, 1991). Overall, "In most but not all instances, the relationship is linear, showing that more advanced or more proficient students use strategies more frequently" (Oxford & Burry-Stock, 1995, p.10).…”
Section: Discussionmentioning
confidence: 99%
“…Oxford (2003) reports on multiple studies that have used her Strategy Inventory for Language Learning (SILL) to measure the relationship between strategy use and proficiency. Most have found the relationship to be of either a linear (e.g., Green & Oxford, 1995;Oxford & Ehrman, 1995) or curvilinear nature (e.g., Phillips, 1991). Overall, "In most but not all instances, the relationship is linear, showing that more advanced or more proficient students use strategies more frequently" (Oxford & Burry-Stock, 1995, p.10).…”
Section: Discussionmentioning
confidence: 99%
“…Brown and Palincsar (1985) suggested that an effective reading instruction program should require the identification of complementary strategies that are modeled by an expert and acquired by the learner in a context reinforcing the usefulness of such strategies .Unskilled readers can become skilled readers and learners of whole text if they are given instruction in effective strategies and taught to monitor and check their comprehension while reading with respect to this point, Al Melhi (2000)has found that some differences do exist between skilled and less skilled readers in terms of their actual and reported reading strategies, their use of global reading strategies (such as underlining, guessing, reading twice ), their metacognitive awareness, their perception of a good reader, and their self-confidence as readers. Training in metacognitive language learning strategies help learners develop their reading skills and raise their language proficiency levels (Palinscar, 1986;Green& Oxford, 1995;Carrell, Gajdusek &Wise;.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…That is, it sought to find if there is a relationship between the learner's preferences in learning a language (visual, auditory, and kinetic) which is proposed by Reid (1987) and the strategies used by learners which were mainly based on Oxford (1990 a) that was enriched by ideas from Green and Oxford (1995), and Khaldie (2000) which consisted of strategies including memory, cognitive, compensation, metacognitive, affective, and social.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…The first was Reid's (1987) learning style questionnaire. The other instrument was Strategy Inventory for Language Learning taken from Oxford's (80-item strategy inventory for language learning (SILL), enriched by ideas from Green and Oxford (1995), and Khaldie (2000), which was ultimately based on Oxford's (1990a) classification of language learning strategies.…”
Section: Data Collection and Scoringmentioning
confidence: 99%